RBC, HB, HCT, CRP, and ESR at different postoperative periods after the application of intravenous unit dose transient acid in PLIF: A case control study - Hao, Shenshen; Wang, Xiangping; Yue, Zenan; Zhang, Ruijun; Wang, Pengcheng; Meng, Saike; Liu, Shuai; Li, Hongke; Dong, Shengli (Frontiers in Surgery, 2023)
Background: Tranexamic acid (TXA) has been used in posterior lumbar interbody fusion (PLIF) and reduces blood loss. However, it has not been reported whether it will continue to affect postoperative red blood cells (RBC), hemoglobin (HB), hematocrit (HCT), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). The purpose of this study was to observed the above indicators at different time after PLIF with unit dose intravenous (iv) TXA. Methods: The data of 44 patients treated by single-segment PLIF from 2020.11 to 2022.3 were retrospectively analyzed. Observation group was given a unit dose of ivTXA (1g/100ml) 15 minutes before skin incision after general anesthesia. Patients without TXA were recorded as control group. Main observation indicators include RBC, HB, HCT, CRP and ESR on the 1st, 4th, 7th and last tested day after surgery. Secondary observation indicators include postoperative activated partial thrombin time (APTT), prothrombin time (PT), thrombin time (TT), and fibrinogen (FIB); and operation time, intraoperative blood loss, postoperative drainage volume, incision healing, postoperative deep vein thrombosis and postoperative hospital stay. Results: The operation was successfully completed without related complications. At term of main observation indicators, RBC, HB and HCT remained relatively stable, while CRP and ESR fluctuated to some extent after PLIF. The RBC, HB and HCT in the observation group were higher than those in the control group with statistically significant (p<0.05). Except the CRP of 7th postoperative day of the observation group was significantly lower than that of the control group (p<0.05), there was no difference in other CRP and ESR between the two groups (p>0.05). At term of secondary observation indicators, the intraoperative blood loss and postoperative drainage volume of the observation group were lower than those of the control group with statistically significant (p<0.05). There was no significant difference in postoperative APTT, PT, TT, FIB, and operation time and postoperative hospital stay between the two groups (p>0.05). Conclusion: The application of unit dose of ivTXA in PLIF can safely and effectively reduce blood loss. Meanwhile, it can also maintain higher RBC, HB, HCT levels without disturbing CRP and ESR levels after surgery.